Fabrication and Magnetic Properties of \(Nd_2Fe_14B/Fe_65Co_35\) Hard Magnetic Ribbons - Truong, Nguyen Xuan; Khanh, Nguyen Van (Communications in Physics, 2013)
Nd\(_2\)Fe\(_14\)B/Fe\(_65\)Co\(_35\) hard magnetic ribbons were fabricated by melt-spinning technique using Nd\(_16\)Fe\(_76\)B\(_8 \) and Fe\(_65\)Co\(_35\) pre-alloys as starting materials. The results showed that the formation of the interactive hard/soft nanocomposite with the homogeneous distribution of the Fe-Co phase throughout the Nd\(_2\)Fe\(_14\)B matrix provided the Curie temperature (\(T_c)\) as high as 747 K, the magnetic remanence (B\(_r\)) of 8.88 kG and the maximum energy product, (BH)\(_\), of 16.75 MG.Oe for the fabricated Nd\(_2\)Fe\(_14\)B/Fe\(_65\)Co\(_35\) ribbons at the optimal speed of 25 m/s. In addition, the intrinsic coercivity (\(_i\)H\(_c\)) of 9.27 kOe and remanence coercivity (\(_b\)H\(_c\)) of 6.94 kOe were found for these ribbons. The roles of the soft Fe\(_65\)Co\(_35\) phase in the increasing of \(T_c\), \(B_r\) as well as in the (00l) preferred crystallographic orientation of hard magnetic grains on the free surface side of the fabricated ribbons were also discussed.